Comparative study on simultaneous leaching of nutrients during bioleaching of heavy metals from sewage sludge using indigenous iron and sulphur oxidising microorganisms. (January 2014) - Pathak, A.; Singh, P.; Dhama, P.; Dastidar, M. G.; Kim, D. J.; Heyes, G.
<x content-type="archive" xml:space="preserve">Abstract</x> The present study investigated the changes in nutrient profile of sewage sludge during bioleaching in a batch mode of operation. The study identified the optimum bioleaching period at which maximum solubilisation of metals is achieved while maintaining the fertilising property of the bioleached sludge. The bioleaching experiments were performed using anaerobically digested sewage sludge by employing indigenous iron and sulphur oxidising microorganisms. The results showed that bioleaching using sulphur oxidising microorganisms is comparatively advantageous due to the higher solubilisation of heavy metals. However, despite its high potential in solubilisation of heavy metals from the sludge, the bioleaching process resulted in the undesirable dissolution/loss of sludge bound nutrients (nitrogen and phosphorus), thus making the sludge less attractive for land application as a fertiliser. After 16 days of bioleaching about 45% of the nitrogen and 34% of the phosphorus were leached from the sludge using indigenous iron oxidising microorganisms, whereas about 78% of the nitrogen and 56% of the phosphorus were leached using indigenous sulphur oxidising microorganisms. The findings indicated that the fertilising property of the sewage sludge can be maintained by conducting the process for a shorter duration of time (up to 10 days). The optimum bioleaching period was 10 days where about 85%Cu, 71%Ni, 91%Zn and 61%Cr were solubilised from the sludge while the loss of nitrogen and phosphorus was only 56 and 51% respectively, by using sulphur oxidising microorganisms. The heavy metals remaining in the bioleached sludge were mostly in the residual fraction ensuring the safe disposal of bioleached sludge for land application as a fertiliser. Cette étude examine les changements du profil de nutriment de boues d'épuration lors de la biolixiviation d'un procédé discontinu. L'étude identifie la durée optimale de biolixiviation à laquelle la solubilisation maximale des métaux est achevée tout en maintenant les propriétés fertilisantes de la boue biolixiviée. On a effectué les expériences de biolixiviation en utilisant des boues d'épuration digérées en condition anaérobique et en employant l'oxydation par ferro- ou thiomicroorganismes indigènes. Les résultats ont montré que la biolixiviation par oxydation avec des thiomicroorganismes était comparativement avantageuse grâce à la solubilisation plus élevée des métaux lourds. Cependant, en dépit de son potentiel élevé de solubilisation des métaux lourds de la boue, le procédé de biolixiviation avait pour résultat une dissolution ou une perte indésirables des nutriments liés dans la boue (azote et phosphore), rendant ainsi la boue moins attrayante pour application dans les champs comme engrais. Après 16 jours de biolixiviation, environ 45% de l'azote et 34% du phosphore étaient lixiviés de la boue par oxydation avec des ferromicroorganismes indigènes, alors qu'environ 78% de l'azote et 56% du phosphore étaient lixiviés en utilisant des thiomicroorganismes indigènes. Les constatations indiquent qu'on peut maintenir les propriétés fertilisantes de la boue d'épuration en effectuant le processus sur une durée plus courte (jusqu'à 10 jours). La période optimale de biolixiviation était de 10 jours, pendant lesquels environ 85% du Cu, 71% du Ni, 91% du Zn et 61% du Cr étaient solubilisés à partir de la boue alors que les pertes d'azote et de phosphore étaient seulement de 56% et de 51%, respectivement, en utilisant les thiomicroorganismes. Les métaux lourds qui restaient dans la boue biolixiviée se trouvaient principalement dans la fraction résiduelle, assurant la disposition sécuritaire comme engrais de la boue biolixiviée.